(untitled) (Jurnal Ipteks Terapan, 2020)
This paper presents the results of chatbot implementation to support mobile learning in higher education. The goal of the chatbot implementation in this study, among others, is to address high interest of higher education in Indonesia toward online learning support mainly during the resent NCOVID19 pandemic in which most of learning process are implemented using online learning mode. The proposed chatbot prototype has been tested in the University of Andalas, Sumatera, Indonesia. The chatbot is designed using standard software engineering method and implemented using Android-based mobile application flatform. Respondents for the chatbot evaluation are chosen based on purposive random sampling among students of Department of Sociology as sampling population. The data collecting is implemented using survey method with self administered questionnaires. The overall evaluation results showed that the designed and implementation has met the students’ expectation. Interestingly most of the respondents showed their interest to use the chatbot